KETERKAITAN KETAHANAN PANGAN DAN PERTUMBUHAN EKONOMI DI KAWASAN INDONESIA TIMUR : STUDI EMPIRIS - Leni Kurnia Optari; Sekar Wulan Amboro Kasih; Helmina Simanjuntak (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study evaluates the influence of the food security index, human development index, and population on economic growth in the Eastern region of Indonesia. The method used in the study is panel data regression with the Fixed Effect Model (FEM) approach. The results of the analysis show that the food security index has no significant effect on economic growth, while the human development index has a positive but insignificant influence. On the contrary, population size has a positive and significant effect on economic growth, emphasizing the importance of market size and labor availability in stimulating economic growth.